Rolling fatigue strength testing device

By designing a device for rolling fatigue strength testing, the device solves the seizure problem in traditional tests by finely controlling the loading mechanism, rotation speed and sliding rate, achieving accurate evaluation under high load conditions and shortening the test time.

JP2025044641APending Publication Date: 2025-04-02NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023152341
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

When evaluating the rolling fatigue strength of high-strength materials, traditional two-cylinder rolling fatigue tests are prone to failing to obtain appropriate test results due to seizure, or the rotation speed needs to be reduced to avoid seizure, resulting in too long test time.

Method used

A rolling fatigue strength test device is designed, which includes a first rotating surface for evaluating the material and a second rotating surface for counteracting the material, which ensures that the test is performed without causing seizure by fine control of the loading mechanism, rotation speed and slip rate.

Benefits of technology

The device can effectively evaluate the rolling fatigue strength of the material under high load conditions, avoiding the occurrence of seizure, shortening the test time, and providing more accurate test results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044641000001_ABST
    Figure 2025044641000001_ABST
Patent Text Reader

Abstract

To provide a rolling fatigue strength testing device which can perform a rolling fatigue strength test without causing seizure of an evaluation material.SOLUTION: A rolling fatigue strength testing device includes a first rotation driving mechanism 300, a mating material 400, a second rotation driving mechanism 500, a loading mechanism 600, a pitching detection part 700, and a control part 900. A diameter D of a second rotation surface 402 of the mating material 400 is 4 mm to 200 mm. At the time of a rolling fatigue strength test, the control part 900 controls the loading mechanism 600 so that a distance x between the second rotation surface 402 and a first rotation axis 301 is 2 mm to 100 mm and a load is within a range of 0.2 kN to 15 kN. In addition, a slip factor σ12 of an evaluation material 1 is set to be -300% to -60% or 60% to 100%, and a seizure evaluation parameter SR is set to be 9.00 or less, by control of the control part 900.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rolling fatigue strength testing device. [Background technology]

[0002] Traditionally, the rolling fatigue strength (pitting strength) of surface-hardened steels used in gears has often been evaluated by a two-cylinder rolling fatigue test, in which a roller-shaped test piece is brought into contact with a mating roller, and the surface pressure on the contact surface and the number of rotations of each roller are controlled to evaluate the rolling fatigue of the test piece.

[0003] For example, in Patent Document 1, pitting strength was measured using a small roller with a diameter of 26 mm and a large roller with a diameter of 130 mm and a crowning of 150 mm as test specimens, with a slip ratio of 80%, a rotation speed of the small roller of 1000 rpm, and a surface pressure of 2800 MPa or 3000 MPa. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-132936 A [Non-patent literature]

[0005] [Non-Patent Document 1] Ichiro Nakahara, Mechanics of Materials, Vol. 2, Yokendo, Tokyo (1971), pp. 116-132 [Non-Patent Document 2] Masatoshi Tokuda, Mechanical Design, Vol. 24, No. 12 (1980), pp. 26-30 [Non-Patent Document 3] Tedric A. Harris, "Rolling Bearing Analysis", John Wiley & Sons Inc., p.110-143. Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, electric vehicles have appeared and are increasing their share of the market. In electric vehicles, the load on the gears (surface pressure, rotation speed, slip ratio, etc.) tends to be higher than in conventional gasoline engine vehicles, so the steel used to make the gears also requires high strength. As a result, when evaluating steel materials used as gears in electric vehicles, it has become necessary to carry out tests under higher loads.

[0007] In the conventional twin-cylinder rolling fatigue test, when evaluating the rolling fatigue strength of high-strength materials under high load, seizure can occur during the test. This can result in poor test results, or the rotation speed must be reduced to avoid seizure, resulting in a long test time.

[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a rolling fatigue strength testing device that can perform rolling fatigue strength testing without causing seizure of the evaluation material. [Means for solving the problem]

[0009] The gist of the present invention, which has been completed based on the above findings, is as follows. [1] A rolling fatigue strength testing apparatus according to one aspect of the present invention comprises: A test device for evaluating the rolling fatigue strength of an evaluation material having a first rotation surface formed around a center line, A first rotation drive mechanism that holds the evaluation material and rotates the evaluation material around a first rotation axis that is coaxial with the center line; a mating member having a second surface of rotation centered on a second axis of rotation; a second rotation drive mechanism that holds the counter member so that the second rotation axis is parallel to the first rotation axis and rotates the counter member about the second rotation axis; a load applying mechanism that moves the first rotation drive mechanism and the second rotation drive mechanism relatively closer to and farther from each other while rotating the first rotation surface and the second rotation surface in opposite directions to each other in a state where the first rotation surface and the second rotation surface face each other; A pitting detection unit that detects pitting occurring on the first rotation surface of the evaluation material; A control unit that controls the first rotation drive mechanism, the second rotation drive mechanism, and the load application mechanism; Equipped with The diameter D of the second rotation surface of the mating member is 4 mm to 200 mm, During a rolling fatigue strength test in which a load is applied from the counter member to the evaluation member by the load application mechanism while performing the reverse rotation, A distance x between the second rotation plane and the first rotation axis is 2 mm to 100 mm; The control unit controls the load application mechanism so that the load is within a range of 0.2 kN to 15 kN. The control unit controls the first rotation drive mechanism, the second rotation drive mechanism, and the load application mechanism, The slip ratio σ of the evaluation material is calculated by the following formula (1): 12 Set to -300% to -60% or 60% to 100%, The image sticking evaluation parameter S is calculated using the following formula (2). R shall be 9.00 or less. σ 12 =[%]=(2×π×R 11 ×u1 / 60-2×π×R 21 ×u2 / 60) / (2×π×R 11 ×u1 / 60) (Formula 1) S R =A(σ 12 / 100) 2 ...(Formula 2) R 11 : Radius of the first rotation surface from the first rotation axis [mm] R 21 : Radius of the second surface of rotation from the second axis of rotation [mm] u1: Rotation speed of the evaluation material [rpm] u2: Rotational speed of the mating material [rpm] A: Contact area [mm 2 ]

[0010] [2] The rolling fatigue strength test apparatus according to the above item [1] may be configured as follows: The root mean square roughness Rq of the contact surface of the evaluation material that comes into contact with the counter material and the contact surface of the counter material that comes into contact with the evaluation material is 1.00 μm or less, During the rolling fatigue strength test, the control unit controls the first rotation drive mechanism, the second rotation drive mechanism, and the load application mechanism, The yield parameter R is calculated using the following formula (3): D be 0.85 or less. R D =Dτ xy ' / D c ...(Formula 3) Dτ xy '=2×Dτ xy ...(Formula 4) Where: R D : Conjugate maximum shear stress τ of the evaluation material xy At a depth position Dτ from the contact surface of the evaluation material, xy Dτ calculated from the above (Equation 4) using xy ' and the effective hardened layer depth D of the evaluation material c and the yield parameter calculated by

[0011] [3] In the rolling fatigue strength testing apparatus described in [2] above, The radius R of the first surface of revolution 11 may be 2 to 100 mm.

[0012] [4] The rolling fatigue strength test device according to any one of the above items [1] to [3] may be configured as follows: The diameter D of the second rotation surface of the mating member is 4 mm to 200 mm, The inter-axis distance d between the first rotation axis and the second rotation axis is 20 mm to 58 mm, The y value calculated by the following formula 5 is 0.75 or less. y=2d / D-1 (Eq. 5)

[0013] [5] In the rolling fatigue strength testing apparatus according to any one of the above [1] to [4], The crowning radius of the mating material 22 may be 1 mm or more.

[0014] [6] In the rolling fatigue strength testing apparatus described in [5] above, The second rotational axis of the mating member is located along the second rotational axis and the crowning R 22 Length dimension l excluding the part 21 may be 2 mm or more. Effect of the Invention

[0015] According to the rolling fatigue strength testing device described in the above aspect of the present invention, a rolling fatigue strength test can be performed without causing seizure of the evaluation material. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a plan view of a rolling fatigue strength testing device according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing the rolling fatigue strength testing device, and is a vertical sectional view taken along the line AA in FIG. [Diagram 3] FIG. 2 is a schematic diagram for explaining a rolling fatigue strength test using the rolling fatigue strength test apparatus. [Figure 4] FIG. 2 is a schematic diagram illustrating a major axis radius a and a minor axis radius b of a contact surface of a material to be evaluated using the rolling fatigue strength testing device. [Diagram 5] FIG. 2 is a front view showing a test material to be evaluated by the rolling fatigue strength testing device. [Figure 6] FIG. 2 is a front view of a counterpart member provided in the rolling fatigue strength testing device. [Figure 7] FIG. 2 is a schematic side view of an evaluation material and a counterpart material during a rolling fatigue strength test, as viewed from a line of sight parallel to a first rotation axis and a second rotation axis. [Figure 8] 4 is a flowchart showing the control process of the rolling fatigue strength testing apparatus. [Figure 9] FIG. 6 is a front view showing an evaluation material to be evaluated by a rolling fatigue strength testing device according to a second embodiment of the present invention. [Figure 10] FIG. 2 is a front view of a mating member provided in the rolling fatigue strength testing device. [Figure 11] 10 is a schematic diagram illustrating the contact length Ls and the contact width 2w on the contact surface of the evaluation material of FIG. 9. FIG. [Figure 12] FIG. 13 is a front view showing a modified example of the evaluation material. [Figure 13] FIG. 13 is a front view showing another modified example of the evaluation material. [Figure 14] FIG. 13 is a front view showing a modified example of the counterpart member. [Figure 15] FIG. 13 is a front view showing another modified example of the counterpart member. [Figure 16] FIG. 13 is a front view showing still another modified example of the evaluation material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, embodiments and modifications of the rolling fatigue strength testing device of the present invention will be described with reference to the drawings.

[0018] <First embodiment> Before describing the rolling fatigue strength test device of this embodiment shown in Figures 1 and 2, an overview of the rolling fatigue strength test using the device will be described with reference to Figures 3 and 4. For the sake of explanation, Figure 3 shows only a portion of the evaluation material 1 that comes into contact with the counterpart material 2. In this rolling fatigue strength test, as shown in Fig. 3, a first rotation surface 111 of a cylindrical evaluation material 1 having a rotation axis C1 is brought into contact with a second rotation surface 211 of a cylindrical mating material 2 having a rotation axis C2, and while a load is applied from the mating material 2 to the evaluation material 1, the evaluation material 1 and the mating material 2 are rotated in opposite directions to each other, thereby evaluating the rolling fatigue strength of the evaluation material 1. The contact surface S between the evaluation material 1 and the mating material 2 shown in Fig. 4 is the contact surface of the evaluation material 1 in a state in which a load is applied from the second rotation surface 211 of the mating material 2 to the first rotation surface 111 of the evaluation material 1.

[0019] In this rolling fatigue strength testing device, the evaluation material 1 and the mating material 2 are rotated at independent rotational speeds while maintaining contact. In other words, by rotating the evaluation material 1 and the mating material 2 in opposite directions at different circumferential speeds, slippage occurs between the first rotation surface 111 and the second rotation surface 211, and a test can be performed that reproduces the slippage that occurs in the gear usage environment. Of course, if necessary, it is also possible to rotate the evaluation material 1 and the mating material 2 in opposite directions at the same circumferential speeds and perform a fatigue test without slippage.

[0020] 1 and 2, the rolling fatigue strength test device will be described. Of the above-mentioned evaluation material 1 and counter material 2, the evaluation material 1 is the subject of evaluation, while the counter material 2 constitutes a part of the rolling fatigue strength test device. In the following, for the purpose of facilitating understanding, the counter material 2 will be described with a new reference number 400. The rolling fatigue strength testing device of this embodiment is a testing device for evaluating the rolling fatigue strength of an evaluation material 1 having a first rotation surface 111 formed around a center line (rotation axis C1). This rolling fatigue strength testing device includes a first rotation drive mechanism 300, a counter material 400, a second rotation drive mechanism 500, a load application mechanism 600, a pitting detection unit 700, a lubricant supply mechanism 800, and a control unit 900.

[0021] The first rotation drive mechanism 300 is a mechanism that holds the evaluation material 1 and rotates the evaluation material 1 around a first rotation axis 301 that is coaxial with the center line (the rotation axis C1) of the evaluation material 1. The first rotation drive mechanism 300 has an evaluation material support part 302, a rotation drive shaft 303, a gripper part 304, and a motor 305.

[0022] The evaluation material support part 302 is fixed on a base (not shown) and has a pair of first side walls 302a1, 302a2 that are parallel to each other and spaced apart from each other, and a second side wall 302b that connects the first side walls 302a1, 302a2. The evaluation material support part 302 has a substantially U-shape in a plan view, and supports the evaluation material 1 horizontally within its opening. A bearing (not shown) that supports the rotation drive shaft 303 by inserting it therethrough for free rotation is fixed to the first side wall 302a1. In addition, another bearing (not shown) that is coaxial with the bearing is fixed to the first side wall 302a2. The rotary drive shaft 303 is a shaft body supported by the bearing in the first side wall 302a1, and is supported rotatably while passing through the first side wall 302a1. The gripping portion 304 has a pair of chucks 304a, 304b that coaxially hold one end and the other end of the evaluation material 1. The chuck 304a is fixed to one end of the rotation drive shaft 303 and rotates coaxially together with the rotation drive shaft 303. The chuck 304b is coaxially supported by the other bearing provided on the first side wall 302a2. The chucks 304a, 304b are arranged coaxially and can hold one end and the other end of the evaluation material 1 and release the hold. Motor 305 is fixed onto the base, and its rotation shaft is coaxially connected to the other end of rotation drive shaft 303. The start and stop of rotation, rotation speed, etc. of motor 305 are controlled by control unit 900. The bearings of the first side walls 302a1 and 302a2, the rotary drive shaft 303, the chucks 304a and 304b, and the motor 305 share a common rotation center line, which is a first rotation axis 301. During the rolling fatigue strength test, the evaluation material 1 is supported so as to be rotatable such that its rotation axis C1 is coaxial with the first rotation axis 301.

[0023] The mating member 400 is a rotating body having a second rotation axis 401 and a second rotation plane 402 centered on the second rotation axis 401. The mating member 400 has a main body portion 403, a contact portion 404, and rotation shafts 405a and 405b. The main body 403 is a cylindrical rotating body, and is supported by the second rotary drive mechanism 500 so as to be rotatable about a second rotation axis 401 . The contact portion 404 has a cylindrical shape and is integrally provided at the center position in the axial direction of the main body portion 403, and is rotatable around the second rotation axis 401 integrally with the main body portion 403. The outer diameter dimension of the contact portion 404 is larger than the outer diameter dimension of the main body portion 403. The outer peripheral surface of the contact portion 404 constitutes the second rotation surface 402 that contacts the first rotation surface 111 of the evaluation material 1. The diameter D of the second rotation surface 402 can be, for example, 4 mm to 200 mm. Note that the upper limit value of the diameter D may be 110 mm instead of 200 mm. The rotating shafts 405 a and 405 b are shaft bodies fixed coaxially to one end and the other end of the main body 403 , and are supported by a second rotary drive mechanism 500 .

[0024] The second rotation drive mechanism 500 is a mechanism that holds the counter member 400 and rotates the counter member 400 around a second rotation axis 401. The second rotation drive mechanism 500 has a counter member support portion 501, a base (not shown), a rotation drive shaft 502, and a motor 503. The mating member support portion 501 is fixed on a base described later, and has a pair of first side walls 501a1 and 501a2 that are parallel to each other and spaced apart from each other, and a second side wall 501b that connects the first side walls 501a1 and 501a2. The mating member support portion 501 has a substantially U-shape in a plan view, and supports the mating member 400 in its opening. A bearing (not shown) that supports the rotating shaft 405a rotatably by inserting it therethrough is fixed to the first side wall 501a1. In addition, another bearing (not shown) that is coaxial with the bearing is fixed to the first side wall 501a2. The rotating shaft 405b protrudes to the outside of the mating member support portion 501 by penetrating a bearing provided in the first side wall 501a2. The pedestal is a linear guide (not shown) fixed on the base, and supports the mating member support portion 501 movably along a direction perpendicular to the first rotation axis 301 in a plan view. In other words, by sliding the mating member support portion 501 using the pedestal, the second rotation plane 402 of the mating member 400 can be moved closer to or farther from the first rotation plane 111 of the evaluation member 1. One end of the rotary drive shaft 502 is coaxially connected to the rotary shaft 405b. The motor 503 is fixed to the counterpart member support part 501 via a base (not shown), and its rotation shaft is coaxially connected to the other end of the rotation drive shaft 502. The start and stop of rotation, rotation speed, etc. of the motor 503 are controlled by the control part 900.

[0025] The load applying mechanism 600 is a cylinder fixed on the base, and the tip of its shaft 601 is connected to the second side wall portion 502b. Therefore, by extending the shaft 601, the second rotation plane 402 of the counter member 400 is brought closer to the first rotation plane 111 of the evaluation member 1. Conversely, by shortening the shaft 601, the second rotation plane 402 of the counter member 400 is moved away from the first rotation plane 111 of the evaluation member 1. Furthermore, by extending the shaft 601, the load, which is the pressing force when the second rotation surface 402 of the counterpart material 400 is brought into contact with the first rotation surface 111 of the evaluation material 1, is also adjusted by the fluid pressure (air pressure or hydraulic pressure) that extends the shaft 601. The extension and contraction of the shaft 601 in the load application mechanism 600 and the increase and decrease of the load applied to the evaluation material 1 are controlled by the control unit 900 .

[0026] Specifically, referring to FIG. 7 showing the evaluation material 1 and the mating material 400 during the rolling fatigue strength test, if the diameter of the second rotation surface 402 of the mating material 400 is D (mm), and the axial distance between the first rotation axis 301 and the second rotation axis 401 is d (mm), the diameter D is 4 mm to 200 mm, the axial distance d is 20 mm to 58 mm, and the y value calculated by the following (Equation 5) is 0.75 or less. Here, the y value is a dimensionless value, and by setting it to 0.75 or less, it is possible to obtain the advantage of preventing the mating material from pitching before the evaluation material. The more preferable upper limit of the y value is 0.50, and the most preferable upper limit is 0.30. y=2d / D-1 (Eq. 5)

[0027] The pitching detection unit 700 includes a torque sensor 701 and a vibration sensor 702 . Torque sensor 701 is provided on rotation drive shaft 303 of first rotation drive mechanism 300, and measures fluctuations in the torque value acting on rotation drive shaft 303 during a rolling fatigue strength test. The measured torque value is transmitted to control unit 900 in real time. The vibration sensor 702 is provided on the evaluation material support part 302 of the first rotation drive mechanism 300, and measures the vibration value generated in the evaluation material 1 during the rolling fatigue strength test via the vibration of the evaluation material support part 302. The measured vibration value is transmitted to the control unit 900 in real time. The control unit 900 performs analysis using the torque value received from the torque sensor 701 and the vibration value received from the vibration sensor 702 as input, and detects in real time whether or not pitching has occurred in the evaluation material 1.

[0028] The lubricant supply mechanism 800 includes a lubricant reservoir 801 , a pump 802 , a nozzle 803 , and a pipe 804 . The lubricant oil reservoir 801 is a tank that stores the lubricant oil to be supplied to the evaluation member 1 and the counterpart member 400 . The pump 802 pumps the lubricant in the lubricant reservoir 801 toward the nozzle 803 . The nozzle 803 is disposed directly below the contact position between the first rotation surface 111 of the evaluation member 1 and the second rotation surface 402 of the counterpart member 400. The outlet opening of the nozzle 803 faces vertically upward so as to face the contact position. Pipes 804 connect between the lubricant oil reservoir 801 and the pump 802 and between the pump 802 and the nozzle 803 , respectively, and enable the supply of lubricant oil from the lubricant oil reservoir 801 to the nozzle 803 . The pump 802 is controlled by the control unit 900. That is, when the pump 802 receives an instruction from the control unit 900 to supply the lubricant, the pump 802 takes in the lubricant from the lubricant supply mechanism 800 and then pumps it toward the nozzle 803. As a result, the lubricant is sprayed from the nozzle 803 to the contact position between the first rotation surface 111 of the evaluation member 1 and the second rotation surface 402 of the counterpart member 400.

[0029] As described above, the rolling fatigue strength testing device of this embodiment is a testing device for evaluating the rolling fatigue strength of the evaluation material 1 having the first rotation surface 111 formed around the rotation axis C1, which is the center line. This rolling fatigue strength testing device includes a first rotation drive mechanism 300 that holds the evaluation material 1 and rotates the evaluation material 1 around the first rotation axis 301 that is coaxial with the center line, a mating material 400 that has a second rotation surface 402 centered on a second rotation axis 401, and a second rotation drive mechanism 50 that holds the mating material 400 so that the second rotation axis 401 is parallel to the first rotation axis 301 and rotates the mating material 400 around the second rotation axis 401. The evaluation material 1 is equipped with a load application mechanism 600 that moves the first rotation drive mechanism 300 and the second rotation drive mechanism 500 relatively closer to and farther from each other while rotating the first rotation surface 111 and the second rotation surface 402 in opposite directions while facing each other, a pitting detection unit 700 that detects pitting that occurs on the first rotation surface 111 of the evaluation material 1, and a control unit 900 that controls the first rotation drive mechanism 300, the second rotation drive mechanism 500, and the load application mechanism 600.

[0030] Furthermore, in the rolling fatigue strength testing device of this embodiment, the diameter D of the second rotation surface 402 of the counterpart material 400 is 4 mm to 200 mm. Also, during the rolling fatigue strength test in which a load is applied from the counterpart material 400 to the evaluation material 1 by the load applying mechanism 600 while performing the reverse rotation, a configuration is adopted in which the control unit 900 controls the load applying mechanism 600 so that the distance x between the second rotation surface 402 and the first rotation axis 301 is 2 mm to 100 mm and the load is within a range of 0.2 kN to 15 kN.

[0031] Although details will be described later, in the rolling fatigue strength testing device of this embodiment, the control unit 900 controls the first rotation drive mechanism 300, the second rotation drive mechanism 500, and the load application mechanism 600 to obtain the slip ratio σ of the evaluation material 1. 12 and the image sticking evaluation parameter S R Specifically, the slip ratio σ of the evaluation material 1 calculated by the following (Equation 1) is controlled. 12 In addition, the image sticking evaluation parameter S calculated by the following (Equation 2) is set to be −300% to −60% or 60% to 100%. R shall be 9.00 or less. σ 12 =[%]=(2×π×R 11 ×u1 / 60-2×π×R 21 ×u2 / 60) / (2×π×R 11 ×u1 / 60) (Formula 1) S R =A(σ 12 / 100) 2 ...(Formula 2) Here, the variables are as follows: R 11 : Radius of the first rotation surface from the first rotation axis [mm] R 21 : Radius of the second surface of rotation from the second axis of rotation [mm] u1: Rotation speed of the evaluation material [rpm] u2: Rotational speed of the mating material [rpm] A: Contact area [mm 2 ]

[0032] In the rolling fatigue strength test device of this embodiment, the root mean square roughness Rq of the contact surface of the evaluation material 1 that comes into contact with the counterpart material 400 and the contact surface of the counterpart material 400 that comes into contact with the evaluation material 1 is set to 1.00 μm or less. During the rolling fatigue strength test, the control unit 900 controls the first rotation drive mechanism 300, the second rotation drive mechanism 500, and the load application mechanism 600 to obtain a yield parameter R D is set to 0.85 or less. R D =Dτ xy ' / D c ...(Formula 3) Dτ xy '=2×Dτ xy ...(Formula 4) Where: R D : Conjugate maximum shear stress τ of the evaluation material xy At a depth position Dτ from the contact surface of the evaluation material, xy Dτ calculated from the above (Equation 4) using xy ' and the effective hardened layer depth D of the evaluation material c and the yield parameter calculated by

[0033] The detailed operation of the rolling fatigue strength testing device will be described later with reference to the flow chart of FIG. Before that, in order to prevent burn-in of the evaluation material 1, the burn-in evaluation parameter S used in the control operation of each device by the control unit 900 is R The following will be explained first.

[0034] [Image sticking evaluation parameter S R is 9.00 or less] In the rolling fatigue strength test according to this embodiment, the contact area A (mm 2 ) and slip ratio σ 12 Therefore, S calculated from equation (1) R The control unit 900 controls each device so that S is 9.00 or less. Ris a parameter related to the seizure of the first rotation surface 111 of the evaluation material 1, and is expressed in mm 2 It is.

[0035] S R =A(σ 12 / 100) 2 ...Equation (1)

[0036] For example, when the contact portion 404 of the counter material 400 is in a crown shape in which the contact portion 404 that contacts the evaluation material 1 is gradually convex from the end toward the center as shown in FIG. 6, the contact surface S of the evaluation material 1 with the counter material 400 is elliptical as shown in FIG. 4. The major axis radius of the elliptical contact surface S is the major axis radius a (mm), and the minor axis radius of the ellipse is the minor axis radius b (mm). Using the major axis radius a (mm) and the minor axis radius b (mm), the contact area A of the contact surface S is expressed by the following formula (2). The major axis of the contact surface S is parallel to the rotation axis C1 of the evaluation material 1, and the minor axis of the contact surface S is perpendicular to the major axis of the contact surface S at the contact surface S.

[0037] A=π×a×b...Equation (2)

[0038] The major axis radius a and the minor axis radius b are calculated by a method based on Non-Patent Document 1 (Ichiro Nakahara, Material Mechanics, Volume 2, Yokendo, Tokyo (1971), pages 116-132).

[0039] Slip ratio σ 12 is the relative circumferential speed of the evaluation member 1 with respect to the counterpart member 400, and is expressed by the following formula (3).

[0040] σ 12 [%] = (2 × π × R 11 ×u1 / 60-2×π×R 21 ×u2 / 60) / (2×π×R 11 ×u1 / 60)...Equation (3) Where: R 11 : Radius perpendicular to the rotation axis C1 of the contact portion 11 in the evaluation material 1 R 21: Radius perpendicular to the rotation axis C2 (i.e., the second rotation axis 401) of the contact portion 404 of the counter member 400 u1: Rotation speed of evaluation material 1 [rpm] u2: Rotational speed of the mating material 400 [rpm] It is.

[0041] In the above formula (3), 2 × π × R 11 ×u1 / 60 represents the peripheral speed (m / s) at the minimum radius position in the contact portion 11 of the evaluation material 1, and 2×π×R 21 ×u2 / 60 represents the circumferential speed (m / s) at the maximum radius position in the contact portion 404 of the counterpart material 400.

[0042] Burn-in evaluation parameter S R is 9.00 or less. Image sticking evaluation parameter S R If the seizure evaluation parameter S exceeds 9.00, the amount of heat generated by friction occurring at the contact surface between the evaluation material 1 and the mating material 400 increases, causing the oil film to break and seizure to occur between the evaluation material 1 and the mating material 400. R From the viewpoint of preventing image sticking, the image sticking evaluation parameter S is preferably 8.50 or less, and more preferably 8.00 or less. R The lower limit of the image sticking evaluation parameter S R A small value means a small test load, which leads to a long test time. R is preferably 0.05 or more, and more preferably 0.10 or more.

[0043] From the above formulas (1) to (3), the image sticking evaluation parameter S R In order to make the value of the major axis radius a, the minor axis radius b, and the radius R of the cross section perpendicular to the rotation axis C1 at the contact portion 11 of the evaluation material 1 are 11 (See FIG. 5 ), the radius R of a cross section perpendicular to the rotation axis C2 at the contact portion 404 of the mating member 400 21(See FIG. 6 ), the rotation speed u1 at the contact portion 11 of the evaluation member 1 and the rotation speed u2 at the contact portion 404 of the counterpart member 400 may be changed. Here, the rotation speed u1 and the rotation speed u2 can be obtained by the control unit 900 controlling the rotation speeds of the motors 305 and 503 individually.

[0044] [Slip ratio σ 12 -300~-60% or 60%~100% As described above, in this embodiment, the image sticking evaluation parameter S R The measurement conditions are set using the above. This is done by checking the harmony between the major axis radius a and the minor axis radius b of the contact surface S, which are calculated based on the shape and material of the evaluation material 1 and the mating material 400, and the applied load, and by determining the slip ratio σ 12 That is, the image sticking evaluation parameter S R is within the range where the slip ratio σ is 9.00 or less (i.e., within the range where burn-in can be suppressed). 12 It is possible to set a small value (a value where the slip ratio is large) and a slip ratio σ smaller than -60% (a value where the slip ratio is large) 12 Even when the test is performed under high load, seizure can be suppressed. 12 The test could be carried out without any problems down to a minimum of -300%. 12 is preferably −280% or more, and more preferably −260% or more. In addition, the slip ratio σ 12 may be set to 60% to 100%.

[0045] In the case of gears used in electric vehicles as envisioned in this disclosure, the slip ratio σ 12 As described above, in this embodiment, the slip ratio σ 12 To more accurately reproduce the environment in which gears are used, the slip ratio σ 12is preferably −80% or less, more preferably −100% or less, or −120% or less.

[0046] Incidentally, in a rolling fatigue strength test, when evaluating a steel material that is to be used for a gear that is to be surface-hardened (particularly gas carburizing, vacuum carburizing or nitriding), an evaluation material 1 that has been surface-hardened under the same conditions as the gear is used. Here, if the test is performed with an excessively high load applied from the mating material 400 to the evaluation material 1, the inside of the evaluation material may undergo plastic deformation during the test, which may affect the test results of the surface fatigue strength. This plastic deformation is a separate issue from preventing seizure, but the inventors have determined that a seizure evaluation parameter S R It was found that more accurate test results could be obtained by combining control by a different control parameter with control by the other control parameter. That is, the inventors have investigated the problem of plastic deformation and have found that in the conventional two-cylinder test, shear stress acts at a deep position from the surface, and as a result, plastic deformation occurs at a deep position where the effect of surface hardening treatment cannot reach. D By appropriately adjusting the load, it was possible to prevent internal plastic deformation even during high-load tests.

[0047] [Yield parameter R D is 0.85 or less] The rolling fatigue strength test method according to the present embodiment is xy Dτ calculated from equation (4) xy ' and the effective hardened layer depth D at the contact portion 11 of the evaluation material 1 c and the yield parameter R calculated from equation (5) D is 0.85 or less. Dτ xy is the maximum conjugate shear stress τ xy This is the depth position from the contact surface S in the contact portion 11 of the evaluation material 1 when a load is applied, at which point the

[0048] Dτ xy '=2×Dτ xy ...Equation (4) R D =Dτ xy ' / D c ...Equation (5)

[0049] A shear stress acts on the contact surface S, and a conjugate shear stress acts from the contact surface S toward the inside. The conjugate shear stress causes fatigue cracks to occur inside the contact surface S, and the first rotation surface 111 of the evaluation material 1 peels off and wears away. The shear stress on the contact surface S occurs near the boundary of the contact surface S, and the conjugate shear stress is 0 on the surface and reaches a maximum value τ max become.

[0050] In a two-roller rolling fatigue test conducted under conditions of low slip ratio, the tangential force is relatively small compared to that of gears, so pitting does not occur unless the test surface pressure is increased to increase the frictional force of the contact area. Therefore, in a two-roller rolling fatigue test with increased surface pressure, the effect of the above-mentioned conjugate shear stress cannot be ignored.

[0051] Maximum conjugate shear stress τ xy The depth position (maximum conjugate shear stress position) Dτ from the contact surface S where xy is a value corresponding to z0 described in Non-Patent Document 2 (Tokuda Masatoshi, Machine Design, Vol. 24, No. 12 (1980), pp. 26-30). Specifically, it is expressed by the following formula (6).

[0052]

number

[0053] In the above formula (6), b is the minor axis radius of the contact surface S, and t is a value calculated by the following formula (7).

[0054]

number

[0055] In the above formula (7), b is the minor axis radius of the contact surface S, and a is the major axis radius of the contact surface S. Moreover, the above formula (7) is an equation obtained by modifying the following formula (8) shown in Non-Patent Document 2. Note that the above is written on the assumption that the shape of the contact surface S is an ellipse. The case where the shape of the contact surface S is rectangular will be described later.

[0056]

number

[0057] D in Equation (5) c is the effective hardened layer depth at the contact portion of the evaluation material 1, specifically, the depth from the first rotation surface 111 of the evaluation material 1 to the position where the Vickers hardness is 513 Hv.

[0058] Effective hardened layer depth D of evaluation material 1 c is calculated by the following method. That is, a cross section perpendicular to the rotation axis C1 from the center position of the contact portion 11 of the evaluation material 1 is obtained, and in each cross section, the Vickers hardness Hv is measured starting from a position 0.03 mm in the depth direction from the contact surface, 0.05 mm, 0.10 mm, and every 0.05 mm thereafter to a depth of 2.00 mm in accordance with JIS Z2244:2020 with a load of 0.20 kgf. The measurement positions are three positions in the circumferential direction on the cross section at 120° intervals, and the average value of the radial length (depth) up to the position where the measured Vickers hardness Hv is 513 Hv is defined as the effective hardened layer depth D c Let us assume that.

[0059] The yield parameter R expressed by equation (5) D If R exceeds 0.85, the conjugate shear stress occurring in the effective hardened layer of the evaluation material 1 is relatively too high inside the effective hardened layer, and yielding occurs inside the evaluation material 1. As a result, the inside of the evaluation material 1 hardens, and pitting originating from the inside of the evaluation material 1 occurs due to the hardening, and it is not possible to accurately reproduce a test simulating the usage environment of a gear. D R should be 0.85 or less. D is preferably 0.75 or less, and more preferably 0.70 or less.

[0060] [Evaluation material 1] Next, the evaluation material 1 will be described in detail. The evaluation material 1 is, for example, made of surface-hardened steel in which the surface is harder than the interior. Surface-hardened steel is a steel material used, for example, for gears of electric vehicles. For example, a steel material in which the C concentration at the surface is higher than the C concentration at the interior and the surface is hardened, or a steel material in which the N concentration at the surface is higher than the N concentration at the interior and the surface is hardened, is used as the evaluation material 1, and the rolling fatigue strength is evaluated.

[0061] Table 1 shows the distribution of Vickers hardness Hv of a surface-hardened steel for which rolling fatigue strength is evaluated as an example of evaluation material 1. Vickers hardness Hv was measured in accordance with JIS Z2244:2020, with a load of 0.20 kgf, at the distance from the surface shown in Table 1. It can be seen that in surface-hardened steel surface-hardened by gas carburizing, vacuum carburizing, or nitriding, the Vickers hardness Hv decreases toward the inside. In the example shown in Table 1, the effective hardened layer depth D of a surface-hardened material surface-hardened by gas carburizing is C (ECD in Table 1) is 0.77 mm, and the effective hardened layer depth D of the surface-hardened material hardened by vacuum carburizing C (ECD in Table 1) is 0.45 mm, and the effective hardened layer depth D of the surface-hardened material that has been surface-hardened by nitriding C (ECD in Table 1) is 0.14 mm.

[0062] [Table 1]

[0063] Next, the shape of the evaluation material 1 will be described in detail with reference to FIG. 5. FIG. 5 is a front view of the evaluation material 1. The evaluation material 1 is substantially cylindrical with a rotation axis C1, and the shape of a cross section perpendicular to the rotation axis C1 is circular at any position along the rotation axis C1. The evaluation material 1 includes a contact portion 11 that is a portion that contacts the counter material 400, and a main body portion 12 connected to both ends of the contact portion 11. Hereinafter, the direction along the rotation axis C1 may be referred to as the axial direction, and the direction perpendicular to the rotation axis C1 may be referred to as the radial direction.

[0064] (Contact part 11) The contact portion 11 is a portion having a smaller diameter than the main body portion 12. The contact portion 11 is provided with a first rotation surface 111 arranged at a radial end portion thereof, which is in contact with the mating member 400. The contact portion 11 is composed of tapered portions 11a, 11a continuing to the main body portion 12, and a cylindrical portion 11b of approximately the same diameter along the rotation axis C1 between the tapered portions 11a, 11a.

[0065] Radius R of contact part 11 in evaluation material 1 11 The radius R of the contact portion 11 is preferably 2 to 100 mm. 11 refers to the minimum radius perpendicular to the rotation axis C1 at the contact portion 11. The radius R of the contact portion 11 11 If the contact area S is 2 mm or more, the area of ​​the contact surface S when the load is applied is small, so that a high surface pressure can be applied with a low load. This allows the maximum shear stress position Dτ xy The radius R of the contact portion 11 can be shifted from the rotation axis C1 side to the contact surface S side. Also, since a high surface pressure can be applied with a low load, the amount of heat generated by friction is reduced, making it difficult for seizure to occur. 11 If the radius R of the contact portion 11 is too small, the contact portion 11 may bend depending on the load, and the amount of bending may become large, resulting in bending fatigue failure. 11 If the radius R of the contact portion 11 is 2 mm or more, the occurrence of bending fatigue fracture can be suppressed. 11 is more preferably 3 mm or more, and further preferably 4 mm or more.

[0066] In addition, the radius R of the contact portion 11 11 If is too large, the area of ​​the contact surface S when the load is applied becomes too large, so it may be necessary to apply a large load in order to apply high surface pressure. When a large load is applied, the maximum shear stress position Dτ xy The contact area 11 may move from the contact surface S side to the rotation axis C1 side, and may yield inside the contact area 11, resulting in work hardening. In addition, when a large load is applied, the amount of heat generated by friction increases, making it more likely to cause seizure. However, when the radius R of the contact area 11 11 By setting the radius R of the contact portion 11 to 100 mm or less, it is possible to suppress yielding inside the contact portion 11 and seizure at the contact surface S. 11 is more preferably 75 mm or less, and further preferably 65 mm or less.

[0067] Crowning R of contact part 11 in evaluation material 1 12 It is preferable that the crowning radius is 1 mm or more. 12 is the radius R of a cross section parallel to the rotation axis C1, including the rotation axis C1 11 The crowning radius of the contact portion 11 is a value represented by the curvature radius of the contact portion 11 at the position having the crowning radius R 12 If the position of maximum shear stress Dτ is 1 mm or more, a high surface pressure can be applied to the first rotation surface 111 with a small load. xy The crowning radius R of the contact portion 11 can be shifted from the rotation axis C1 side to the first rotation surface 111 side. 12 is more preferably 10 mm or more, and further preferably 100 mm or more. 12 If the distance is less than 1 mm, elastic deformation due to contact with the mating material 400 and crowning R due to an increase in the number of repetitions may occur. 12 Wear at the position with crowning radius 12 In the case where the portion other than the portion having the crowning R 12 There is a risk that the outside of the position having this contact will come into contact with the counterpart material 400, causing uneven wear of the contact portion 11.

[0068] Axial length of the contact portion 11 (length in the direction of the rotation axis C1)11 is not particularly limited and may be changed as appropriate. For example, the length l of the contact portion 11 11 may be changed according to the length of the tapered portion 11a of the contact portion 11 in the direction of the rotation axis C1.

[0069] (Root mean square roughness Rq is 1.00μm or less) The root mean square roughness Rq of the first rotation surface 111 in the evaluation material 1 is 1.00 μm or less. If the first rotation surface 111 is too rough, a large convex portion present on the first rotation surface 111 may be plastically deformed during the test to generate a new surface, and seizure may occur on the new surface. However, if the root mean square roughness Rq of the first rotation surface 111 is 1.00 μm or less, there are few large localized convex portions, and seizure can be suppressed. The root mean square roughness Rq of the first rotation surface 111 is preferably 0.90 μm or less, and more preferably 0.80 μm or less. On the other hand, it is preferable that the lower limit of the root mean square roughness Rq of the first rotation surface 111 is small. The root mean square roughness Rq of the first rotation surface 111 may be, for example, 0.02 μm or more, or 0.03 μm or more.

[0070] The root mean square roughness Rq is measured by a method conforming to JIS B0601:2013.

[0071] (Main body 12) The main body 12 is the part that is gripped when performing a rolling fatigue test. The diameter φ and axial length l of the main body 12 are 12 is not particularly restricted.

[0072] [Mating material 400] Next, the contact portion 404 of the counter member 400 will be described in more detail with reference to FIG. 6. FIG. 6 is a front view of the counter member 400. As shown in FIG. 6, the counter member 400 is cylindrical with a rotation axis C2, and the shape of a cross section perpendicular to the rotation axis C2 is circular at any position along the rotation axis C2. The counter member 400 has a contact portion 404 that is a portion that contacts the evaluation member 1. Hereinafter, the direction along the rotation axis C2 may be referred to as the axial direction, and the direction perpendicular to the rotation axis C2 may be referred to as the radial direction.

[0073] (Contact part 404) The contact portion 404 is provided with a second rotation surface 402 that is disposed at a radial end and that comes into contact with the evaluation material 1. The contact portion 404 has a convex crown that is convex when viewed from a direction perpendicular to the rotation axis C2 of the mating material 400. In other words, when viewed from a direction perpendicular to the rotation axis C2 of the mating material 400, the contact portion 404 has a diameter (the distance from the rotation axis C2 to the second rotation surface 402) that increases from both axial ends toward the axial center.

[0074] Radius R of the contact portion 404 of the mating member 400 21 The radius R of the contact portion 404 is preferably 2 to 100 mm. 21 refers to the maximum radius perpendicular to the rotation axis C2 at the contact portion 404. The radius R 21 If the contact area S is 2 mm or more, the area of ​​the contact surface S is small, so that a high surface pressure can be applied with a small load. xy The contact area 404 can be shifted from the rotation axis C1 side to the first rotation surface 111 side. In addition, since a high surface pressure can be applied with a small load, the amount of heat generated by friction is reduced, and seizure is less likely to occur. 21 If the radius R of the contact portion 404 is too small, it may bend depending on the load, and the amount of bending may become large, resulting in bending fatigue failure. 21 If the radius R of the contact portion 404 is 2 mm or more, the occurrence of bending fatigue fracture can be suppressed. 21is preferably 3 mm or more, and more preferably 4 mm or more.

[0075] In addition, the radius R of the contact portion 404 21 If the surface area of ​​the second rotation surface 402 is too large, a high load may be required to apply a high surface pressure because the surface area of ​​the second rotation surface 402 becomes too large. xy The contact portion 11 of the evaluation material 1 may yield and harden due to the transfer of the force from the first rotation surface 111 side to the shaft side. In addition, when a large load is applied, the amount of heat generated by friction increases, making it more likely to cause seizure. However, when the radius R of the contact portion 404 21 By setting the radius R of the contact portion 404 to 100 mm or less, it is possible to suppress yielding inside the contact portion 11 of the evaluation material 1 and seizure at the second rotation surface 402. 21 is preferably 90 mm or less, and more preferably 80 mm or less.

[0076] Crowning R of the contact portion 404 of the mating member 400 22 It is preferable that the crowning radius is 1 mm or more. 22 is the radius R of a cross section parallel to the rotation axis C2, including the rotation axis C2 21 The crowning radius of the contact portion 404 is a value represented by the radius of curvature of the contact portion 404 at the position having the crowning radius R 22 If the distance between the second surface of rotation 402 and the maximum shear stress position Dτ is 1 mm or more, a small load can be applied to the second surface of rotation 402. xy The crowning radius R of the contact portion 404 can be shifted from the rotation axis C1 side to the first rotation surface 111 side. 22 is preferably 10 mm or more, and more preferably 15 mm or more. 22 If the thickness is less than 1 mm, elastic deformation due to contact with the evaluation material 1 and crowning R due to the increase in the number of repetitions will occur. 22 Wear at the position with crowning radius 22 In cases where the part other than the part having the crowning radius comes into contact with the evaluation material 1, 22There is a risk that the outside of the position having this will come into contact with the evaluation material 1, causing uneven wear of the contact portion 404.

[0077] The root mean square roughness Rq of the second surface of rotation 402 of the mating member 400 is preferably 1.00 μm or less. If the second surface of rotation 402 is too rough, the large convex parts present on the second surface of rotation 402 may be plastically deformed during the test, resulting in new surfaces, which may cause seizure. However, if the root mean square roughness Rq of the second surface of rotation 402 is 1.00 μm or less, there are few large local convex parts, and seizure can be suppressed. The root mean square roughness Rq of the second surface of rotation 402 is more preferably 0.90 μm or less, and even more preferably 0.80 μm or less. On the other hand, it is preferable that the root mean square roughness Rq of the second surface of rotation 402 is small. The root mean square roughness Rq of the second surface of rotation 402 may be, for example, 0.02 μm or more, or 0.03 μm or more.

[0078] The root mean square roughness Rq is measured by a method conforming to JIS B0601:2013.

[0079] So far, we have described the evaluation material 1 and the mating material 400 used in the rolling fatigue testing method according to this embodiment. When a rolling fatigue test is performed, a load is applied from the mating material 400 to the evaluation material 1, and the first rotation surface 111 comes into contact with the second rotation surface 402 of the mating material 400, after which the evaluation material 1 and the mating material 400 rotate in opposite directions at a predetermined speed.

[0080] The above-mentioned evaluation material 1 has a crowning radius 12 The mating material 400 has a crowning R 22 Therefore, stress concentration is less likely to occur compared to the evaluation material 1A and the counterpart material 400A in the second embodiment described later, and more stable test results can be obtained.

[0081] Next, an example of a manufacturing method of the evaluation material and the mating material used in the rolling fatigue test method according to the present embodiment will be described. The manufacturing method of the evaluation material and the mating material described below is merely an example, and the evaluation material and the mating material are not limited to those manufactured by the manufacturing method described below, and the evaluation material and the mating material having the above-mentioned characteristics correspond to the evaluation material and the mating material in the present invention.

[0082] The evaluation material and the counterpart material include an intermediate product manufacturing process in which an intermediate product is manufactured, and a heat treatment process in which the intermediate product is heat treated.

[0083] In the intermediate product manufacturing process, an intermediate product having a predetermined shape is manufactured. For example, molten steel having a predetermined chemical composition is manufactured, and a cast piece (slab or bloom) is manufactured by a continuous casting method using the molten steel. An ingot (steel ingot) may be manufactured by an ingot casting method using the molten steel. Then, the cast piece or ingot is hot worked to manufacture a billet. The billet is hot worked to manufacture a steel bar or wire rod. The hot working may be hot rolling or hot forging. In order to homogenize the crystal grain size of the structure after hot forging, normalizing in accordance with JIS B 6911:2010 "Normalizing and annealing processing of steel" or isothermal annealing (IA) for reducing the material hardness may be performed before the cutting process described later. The manufactured steel bar or wire rod is cold forged or machined to be processed into a predetermined shape to obtain an intermediate product. The machining is, for example, cutting or drilling. The shape of the intermediate product is formed by a well-known method.

[0084] In the heat treatment process, the intermediate product is heat treated. For example, a surface hardening heat treatment is performed on the intermediate product manufactured in the intermediate product manufacturing process. Furthermore, after the surface hardening heat treatment, the intermediate product may be tempered. The intermediate product after quenching may be further machined (cutting, etc.). Surface hardening heat treatment refers to, for example, gas carburizing, vacuum carburizing, nitriding, etc. These treatment conditions are generally known conditions. For the purpose of increasing the compressive residual stress in the surface layer of the part after the surface hardening heat treatment, a surface hardening treatment such as shot peening may be performed.

[0085] Next, the operation of the rolling fatigue strength testing device of this embodiment will be described based on the flowchart in Fig. 8. It is assumed that at the start of the test, the evaluation material 1 is already set in the gripping portion 304 of the first rotation drive mechanism 300 as shown in Figs. First, in step S1, the control unit 900 starts the pump 802, so that the lubricant is sprayed directly upward from the nozzle 803. In the next step S2, the control unit 900 drives the load applying mechanism 600 to extend the shaft 601. As a result, the counterpart member 400 approaches the evaluation member 1 together with the second rotation drive mechanism 500. As a result, in step S3, the second plane of rotation 402 of the counterpart member 400 comes into contact with the first plane of rotation 111 of the evaluation member 1. After this contact, the control unit 900 stops the extension of the shaft 601 once.

[0086] In the following step S4, the control unit 900 causes the motor 305 to start rotating. At the same time, in step S5, the control unit 900 causes the motor 503 to start rotating. In the next step S6, the control unit 900 increases the rotation speed of the motor 305 and the rotation speed of the motor 503, respectively. In the next step S7, the control unit 900 judges whether the rotation speed of the motor 305 and the rotation speed of the motor 503 have reached the set conditions. If the judgment result is NO, the process returns to step S6, and the rotation speed of the motor 305 and the rotation speed of the motor 503 are increased. On the other hand, if the judgment result is YES, the rotation speeds of the evaluation material 1 and the counterpart material 400 are maintained as they are, and the process proceeds to the next step S8. In step S8, the control unit 900 again drives the load application mechanism 600 to extend the shaft 601. In the next step S9, the control unit 900 judges whether the load applied from the second plane of rotation 402 of the counterpart member 400 to the first plane of rotation 111 of the evaluation member 1 has reached the set condition. If the judgment result is NO, the process returns to step S8, and the shaft 601 is further extended to increase the load. On the other hand, if the judgment result is YES, the process proceeds to step S10 while maintaining the load.

[0087] In step S10, the rolling fatigue strength test is continued while keeping constant the rotation speed of the first rotation surface 111 of the evaluation material 1, the rotation speed of the second rotation surface 402 of the counterpart material 400, and the load applied by the second rotation surface 402 to the first rotation surface 111. During this time, the pitting detection unit 700 continues to check whether pitting has occurred in the first rotation surface 111 of the evaluation material 1.

[0088] During the rolling fatigue strength test, if any of the following operation stop patterns is met in step S11, the rolling fatigue strength test is stopped. That is, in step S12, if the control unit 900 determines that "pitching has occurred" based on the information obtained from the pitching detection unit 700, the process proceeds to step S16. Alternatively, in step S13, if a predetermined test condition (eg, test time) is exceeded without confirming the occurrence of pitching, the control unit 900 determines that "pitching has not occurred" and proceeds to step S16. On the other hand, in the case where the control unit 900 finds an operational abnormality in the rolling fatigue strength testing apparatus in step S14, or where the operator of the rolling fatigue strength testing apparatus manually stops the operation in step S15, the process also proceeds to step S16.

[0089] In step S16, the control unit 900 instructs the load applying mechanism 600 to quickly shorten the shaft 601. As a result, the second plane of rotation 402 of the counterpart member 400 quickly separates from the first plane of rotation 111 of the evaluation member 1, and the load is released. In the next step S18, the control unit 900 stops the rotation of the motor 305. This causes the rotation of the evaluation material 1 to stop. At the same time, in step S19, the control unit 900 stops the rotation of the motor 503. As a result, the rotation of the counter member 400 stops. Finally, in step S20, the control unit 900 stops the operation of the pump 802, thereby stopping the spraying of the lubricant from the nozzle 803. After the rolling fatigue strength testing device is stopped, the evaluation material 1 is removed from the gripping portion 304 and then subjected to an inspection to check the presence, size, depth, etc. of pitting.

[0090] <Second embodiment> The second embodiment of the present invention will be described below. In this embodiment, the shapes of the evaluation material and the mating material are particularly different from those of the first embodiment, but the rolling fatigue strength test is performed in the same manner as in the first embodiment, using the rolling fatigue strength test device shown in Fig. 13 according to the procedure shown in Fig. 8. Therefore, the same contents as those in the first embodiment will not be described again, and the following description will focus on the differences.

[0091] The second embodiment differs from the first embodiment in that the shape of the contact surface S of the evaluation material with the counterpart material is parallel to the rotation axis when viewed from the front. This is because the shapes of the evaluation material and the counterpart material are different from those of the first embodiment. The second embodiment will be described below with reference to Figs. 9 to 11. Fig. 9 is a front view of an evaluation material 1A in the second embodiment. Fig. 10 is a front view of a counterpart material 400A in this embodiment. Fig. 11 is a front view of the contact length L at the contact surface S of the evaluation material in this embodiment. s 13 is a schematic diagram for explaining the contact width 2w.

[0092] [Evaluation material 1A] As shown in FIG. 9, the evaluation material 1A has a cylindrical shape, a substantially uniform diameter along the axial direction, and a radius R 11 In other words, the evaluation material 1A is different from the evaluation material 1 in the first embodiment in that the main body and the contact portion are not separated from each other. Therefore, it can be said that the part other than the axial end of the evaluation material 1A is the contact portion 11A.

[0093] The axial length l2 of the contact portion 11A of the evaluation member 1A that comes into contact with the counterpart member 400A is preferably 2 mm or more. Since the evaluation member 1A has a substantially uniform diameter in the direction along the rotation axis C1, the length of the evaluation member 1A in the direction of the rotation axis C1 becomes the axial length l2 of the contact portion 11A. If the axial length l2 of the contact portion 11A is 2 mm or more, the contact area becomes small, and the seizure evaluation parameter S R In addition, by applying a high surface pressure to the first rotation surface 111 with a small load, the maximum shear stress position Dτ xy can be shifted from the rotation axis C1 side to the first rotation plane 111 side. When a plurality of counterpart members 400A are provided, the length of the counterpart member 400A having the shortest length in the direction of the rotation axis C2 of the second rotation surface 402A is set as the thickness t1 of the contact portion 11A, and it is preferable that the thickness t1 is 1 mm or more.

[0094] At both axial ends of the evaluation material 1A, the radius of curvature in plan view is R 13 The shape of the edge 13 is not particularly limited, and may be, for example, R-chamfered, C-chamfered, or light-chamfered. When the shape of the edge 13 is C-chamfered or light-chamfered, the radius of curvature R 13 The center of the circle of curvature is a point equidistant from both ends of the chamfered portion, and the distance from the center to the end of the chamfered portion is the radius of curvature.

[0095] [Mating material 400A] As shown in FIG. 10, the mating member 400A has a cylindrical shape and has a substantially uniform diameter along the axial direction. 22 In other words, the counterpart material 400A is different from the counterpart material 400 in the first embodiment in that the second rotation surface 402A in the contact portion 404A is parallel to the rotation axis C2 of the counterpart material 400A, and is different from the evaluation material 1 in the first embodiment.

[0096] The mating member 400A has a curvature radius R 21 In this case, the axial length l of the second surface of revolution 402A is 21is expressed by the following formula (9), where the axial length of the counterpart material 400A is L2.

[0097] l 21 ≦L2-2×R 21 ...Equation (9)

[0098] The shape of the edge 21a is not particularly limited, and may be, for example, R-chamfered, C-chamfered, or light-chamfered. When the shape of the edge 21a is C-chamfered or light-chamfered, the radius R 21 The center of the circle of curvature is a point equidistant from both ends of the chamfered portion, and the distance from the center to the end of the chamfered portion is the radius of curvature.

[0099] Axial length l of the second surface of revolution 402A 21 It is preferable that the contact area is 2 mm or more. This reduces the contact area, and the burn-in evaluation parameter S R In addition, by applying a high surface pressure to the first rotation surface 111 with a small load, the maximum shear stress position Dτ xy can be shifted from the rotation axis C1 side to the first rotation plane 111 side.

[0100] The above-described evaluation material 1A and counterpart material 400A have simpler shapes than the evaluation material 1 and counterpart material 400 in the first embodiment, respectively, and therefore their preparation is easy.

[0101] [Image sticking evaluation parameter S R ] When a load acts on the evaluation member 1A from the counterpart member 400A, the contact surface S of the evaluation member 1A with the counterpart member 400A becomes a rectangle having a contact width 2w (mm) as shown in FIG. 11. The length of the contact surface S of the evaluation member 1A in the direction of the rotation axis C1 when the load contacts is L. s (mm), the contact area A of the contact surface S is expressed by the following equation (10).

[0102] A=2wL s ...Equation (10)

[0103] The axial length l2 of the contact portion 11A of the evaluation member 1A is longer than the axial length l of the second rotation surface 402A of the counterpart member 400A. 21 When the axial length l of the second rotation surface 402A of the counter member 400A is longer than 21 is the contact length L s The axial length l2 of the contact portion 11A of the evaluation member 1A is the axial length l of the second rotation surface 402A of the counterpart member 400A. 21 When the axial length l2 of the first rotation surface 111A of the evaluation material 1A is shorter than the contact length L s It becomes.

[0104] Burn-in evaluation parameter S R is calculated using the contact area A calculated by the formula (10). R is less than or equal to 9.00.

[0105] [Slip ratio σ 12 -300~-60%, 60~100%] Slip ratio σ of evaluation material 1A 12 is calculated according to the above formula (3). 12 is −300 to −60%, similarly to the first embodiment.

[0106] [Yield parameter R D is 0.85 or less] As described in Non-Patent Document 3, when two cylinders (evaluation material 1A and counterpart material 400A) are in line contact, b / a = 0 (2a → ∞ because crownings R12 and R22 are ∞), and according to the above formula (5), the value of t cannot be 0.5, so according to formula (8), t = 1.00. That is, the conjugate maximum shear stress τ xy The position Dτ in the depth direction from the contact surface S where xy is 0.5b from equation (6). In order to distinguish from the first embodiment, b is conveniently set to w, and the conjugate maximum shear stress τ xy The position D in the depth direction from the contact surface S where τxy would be 0.5w. Yield parameter RD is calculated from the above formulas (4) and (5), and is also 0.85 or less in the second embodiment.

[0107] The evaluation member 1A and the counterpart member 400A may be manufactured in a manner similar to that of the second embodiment.

[0108] The present invention has been described above based on one embodiment of the present invention. As in the first and second embodiments, the image sticking evaluation parameter S R can be calculated by the formula (1). The above-mentioned embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

[0109] <Modification of the first embodiment> For example, in the first embodiment, the evaluation material 1 described above has a shape having a tapered portion 11a, but the evaluation material may be evaluation material 1B having a shape as shown in Fig. 12. In evaluation material 1B, contact portion 11B has a concave crown that is concave when viewed from a direction perpendicular to the rotation axis C1 of evaluation material 1B. In other words, when viewed from a direction perpendicular to the rotation axis C1 of evaluation material 1B, contact portion 11B has a diameter (the distance from the rotation axis C1 to the first rotation surface 111B) that decreases from both axial ends toward the axial center.

[0110] Also, for example, the evaluation material may have a shape as shown in FIG. 13, and the mating material may have a shape as shown in FIG. 14. In the evaluation material 1C shown in FIG. 13, the contact portion 11C is a portion having a larger diameter than the main body portion 12C. In the evaluation material 1C, the contact portion 11C is composed of tapered portions 11c, 11c connected to the main body portion 12C, and a cylindrical portion 11d having approximately the same diameter along the rotation axis C1 between the tapered portions 11c, 11c. On the other hand, in the mating material 400C shown in FIG. 14, the contact portion 404C has a concave crown that is concave when viewed from a direction perpendicular to the rotation axis C2 of the mating material 400C. In other words, the diameter (the distance from the rotation axis C2 to the second rotation surface 402C) of the contact portion 404C becomes smaller from both axial ends toward the axial center when viewed from a direction perpendicular to the rotation axis C2 of the mating material 400C. In addition, when the contact portion 11C has a larger diameter than the main body portion 12C as in the evaluation material 1C, or when the contact portion 11C has a convex crown that is convex when viewed from a direction perpendicular to the rotation axis C1, the radius R of the contact portion 11C is 11 means the maximum radius perpendicular to the rotation axis C1 in the contact portion 11C. In addition, when the contact portion 404 has a concave crown that is concave when viewed from a direction perpendicular to the rotation axis C2, as in the mating member 400C, the radius R of the contact portion 404C is 21 refers to the minimum radius perpendicular to the rotation axis C2 in the contact portion 404C.

[0111] In addition, the counterpart material may have, for example, a main body portion (not shown) on both axial sides of the contact portion, the main body portion having a shape that does not contact the evaluation material.

[0112] In addition, in the rolling fatigue testing method according to the present invention, the number of counterpart materials that are rotated in contact with one evaluation material is not limited to one, and may be multiple.

[0113] <Modification of the second embodiment> Also, for example, in the second embodiment, the above-mentioned mating member 400A has a substantially uniform diameter along the rotation axis C2, but the mating member may be a mating member 400D having a shape as shown in Fig. 15. The mating member 400D is similar to the mating member 400A in that the second rotation surface 402D is parallel to the rotation axis C2 in a front view, but may have a step on the outer periphery other than the second rotation surface 402D.

[0114] In addition, the counterpart material may have, for example, a main body portion (not shown) on both axial sides of the contact portion, the main body portion having a shape that does not come into contact with the evaluation material.

[0115] In addition, the axial length of the contact portion may be appropriately changed within a range in which the contact length of the contact surface of the evaluation material is longer than the contact length of the contact surface of the counter material. For example, the shape of the evaluation material may be evaluation material 1D having a contact portion 11D, which is a portion that contacts the counter material, and a main body portion 12D connected to both ends of the contact portion 11D, as shown in FIG. 16. The contact portion 11D is a portion with a smaller diameter than the main body portion 12D. The contact portion 11D has a first rotation surface 111D arranged at a radial end and that contacts the counter material. The contact portion 11D is composed of a cylindrical portion 11b of approximately the same diameter along the rotation axis C1 between the tapered portions 11a, 11a connected to the main body portion.

[0116] In addition, in the rolling fatigue test method according to the present invention, the number of mating members that are rotated in contact with one evaluation member is not limited to one, and may be multiple. 21 It is preferable that the thickness is 2 mm or more, which can further suppress burn-in. EXAMPLES

[0117] The present invention will be described in more detail below with reference to examples. Note that the examples described below are merely examples of the present invention and are not intended to limit the present invention.

[0118] <Example 1> [Production of evaluation materials] The evaluation materials were manufactured by the following method. Steels SCr420, SCM420, SCM435, SCM822, SNCM220 and SACM645, which have chemical compositions conforming to the JIS G 4053 standard, were melted in a 300 kg vacuum melting furnace to produce molten steel, and each molten steel was cast to produce an ingot. The ingot was hot forged into a round bar with a diameter of 250 mm. Hot forging was performed at a temperature between 1100°C and 1200°C, and after forging, the bar was allowed to cool in the air. Each steel bar (vacuum melted material) was normalized in accordance with JIS B 6911:2010 "Normalizing and annealing processing of steel".

[0119] Next, each normalized steel bar with a diameter of 250 mm was machined to produce evaluation materials having the shapes shown in Figure 5 and Table 2. A main body with a diameter of 24 mm was provided on both axial sides of the contact part. The axial length of each main body was l 12 The length of the contact area l was set to 60 mm. 11 Therefore, the length L of the evaluation material was set to 148 mm.

[0120] [Table 2]

[0121] The prepared evaluation materials were subjected to surface hardening heat treatment by gas carburizing, vacuum carburizing, or nitriding. The conditions for gas carburizing, vacuum carburizing, and nitriding were as follows. That is, in the gas carburizing treatment (gas carburizing quenching and tempering), each evaluation material was held at 930°C for 80 minutes in an atmosphere with a carbon potential CP of 1.0% (carburizing process). Then, the carbon potential CP was set to 0.8%, and the rough test pieces were held at 930°C for 60 minutes (diffusion process). Then, each evaluation material was cooled to 850°C, held at 850°C for 30 minutes, and then cooled in oil at 60°C (quenching process). After cooling, each evaluation material was subjected to tempering treatment. The tempering temperature was 180°C, and the holding time at the tempering temperature was 120 minutes. In the vacuum carburizing treatment, first, a carburizing process was carried out in which acetylene gas was introduced at a furnace pressure of 100 Pa or less. The temperature of the carburizing process was 930°C and the holding time was 30 minutes. After the carburizing process, the diffusion process was carried out. In the diffusion process, the introduction of acetylene gas was stopped and the pressure inside the furnace was set to 10 Pa or less. In the diffusion process, the temperature was 930°C and the holding time was 10 minutes. After the diffusion process, the quenching process was carried out. In the quenching process, the temperature was 850°C and the holding time was 30 minutes. After the holding time, the material was cooled in oil at 60°C. After the quenching process, the tempering process was carried out. In the tempering process, the temperature was 180°C and the holding time was 120 minutes. In the nitriding process, NH3, H2, and N2 gases were introduced into the furnace under atmospheric pressure and held at 570°C for 180 minutes. After the holding time, the material was cooled in oil at 60°C. The Vickers hardness Hv was measured by obtaining 10 cross sections at the contact part of the evaluation material and measuring the hardness distribution. In detail, in each cross section, starting from a position 0.03 mm in the depth direction from the contact surface, the Vickers hardness Hv is measured at 0.05 mm, 0.10 mm, and then every 0.05 mm to a depth of 2.00 mm in accordance with JIS Z2244:2020 under a load of 0.20 kgf. The measurement positions are three positions every 120 degrees on the cross section, and the average value of the radial length (depth) up to the position where the measured Vickers hardness Hv is 513 Hv is defined as the effective hardened layer depth D c It was decided.

[0122] [Manufacturing of counterpart materials] The mating material was manufactured by the following method: Using steel that meets the SCM420 standard of JIS G 4053:2016, the mating material shown in Figure 6 and Table 2 was manufactured by the general manufacturing process, that is, "normalizing → test piece processing → eutectoid carburizing in a gas carburizing furnace → low-temperature tempering → polishing."

[0123] The Vickers hardness Hv at a position 0.05 mm from the surface of the mating material, that is, at a depth of 0.05 mm, was 740 to 760, and the depth at which the Vickers hardness Hv was 513 was in the range of 0.8 to 1.0 mm. The Vickers hardness Hv at a depth of 0.05 mm and the depth at which the Vickers hardness Hv was 513 for each evaluation material were obtained by the following method. That is, a cross section perpendicular to the rotation axis C2 was obtained from the center position of the contact part of the evaluation material, and the Vickers hardness was measured in each cross section at a position 0.03 mm deep from the contact surface, 0.05 mm, 0.10 mm, and every 0.05 mm thereafter to a depth of 2.00 mm in accordance with JIS Z2244:2020 with a load of 0.20 kgf. The hardness values ​​obtained from the measurements were plotted based on the depth of the measurement positions, and the position where the line connecting each point was the target value was identified as the depth where the Vickers hardness Hv was 513.

[0124] [evaluation] The evaluation of seizure and plastic deformation of each of the manufactured evaluation materials was performed by the following method. After finishing of the main body of the evaluation material in order to remove the heat treatment strain, the evaluation material and the mating material were subjected to a two-cylinder rolling fatigue test. The contact surface of the evaluation material and the contact surface of the mating material were brought into contact with each other, and after applying the contact pressure p0 shown in Table 3, they were rotated in opposite directions at the rotation speed shown in Table 3. The contact pressure p0 shown in the table was calculated by the following formula (11) shown in formula (6.49) in Non-Patent Document 1.

[0125]

number

[0126] In the above formula (11), P is the applied load, a is the major axis radius, and b is the minor axis radius.

[0127] The cutoff number of cycles in the twin cylinder rolling fatigue test is 1.0×10, which indicates the fatigue limit required for general steels. 7 The number of cycles was set to 100. However, if vibration occurred during the test, the rotation of the evaluation material and the mating material was stopped since plastic deformation had occurred inside the evaluation material. If the rotation was stopped before the cut-off number of cycles was reached, the contact surfaces of the evaluation material after the rotation was stopped were observed, and if the test was continued up to the above number of cycles without being stopped midway, the contact surfaces after the test was completed were observed. If no seizure marks were found on these contact surfaces, it was determined that seizure had not occurred. The occurrence of vibration was confirmed using a vibration meter attached to the testing machine.

[0128] The occurrence of plastic deformation inside the evaluation material during the test was confirmed before the test and after the number of repetitions was 1×10 6 After the test, a cross section perpendicular to the rotation axis C1 was obtained from the center position of the contact part of the test material, and the hardness distribution was measured. In detail, in each cross section, starting from a position of 0.050 mm from the contact surface in the depth direction, ΔHv=(1×10 6 The Vickers hardness after the test was subtracted from the Vickers hardness before the test to calculate the average ΔHv at each depth. The largest average ΔHv value at each depth was taken as ΔHv max And ΔHv max If the hardness distribution of the specimen was less than 50Hv, it was determined that there was no plastic deformation inside the specimen. 6 The test pieces used for the measurement of cross-sectional hardness distribution after rolling were different from each other. The results are shown in Table 3.

[0129] [Table 3]

[0130] As described above, the major axis radius a, the minor axis radius b, and the slip ratio σ of the contact surface of the evaluation material with the counter material when a load is applied are 12 Using the above, the image sticking evaluation parameter S is calculated using the formula (1). RIn the cases where the conjugate maximum shear stress τ of the evaluation material was 9.00 or less, no seizure occurred. xy At a depth position Dτ from the contact surface of the evaluation material, xy Dτ calculated from equation (4) using xy ' and the effective hardened layer depth D of the evaluation material c and the yield parameter R calculated from equation (5) D In the example where is 0.85 or less, in addition to no burn-in occurring, 6 No plastic deformation (yielding) occurred inside the evaluation material after the repeated stress cycle. Therefore, the evaluation parameter S R is less than 9.00, and the yield parameter R D It was found that the two-cylinder rolling fatigue test with a coefficient of friction of 0.85 or less can evaluate the rolling fatigue strength of surface-hardened steels used in gears more simply and accurately.

[0131] In Comparative Example 27, the image sticking evaluation parameter S R Because the value exceeded 9.00, seizure occurred on the contact surface of the evaluation material before the cut-off number of repetitions, and appropriate measurement results could not be obtained. Comparative Example 28 has a yield parameter R D was greater than 0.85, so the number of iterations was 1 × 10 6 After this period, plastic deformation occurred inside the evaluation material. In Comparative Example 29, the radius R of the evaluation material 11 The measurement was small, at 1 mm, and the evaluation material was damaged during testing, making it impossible to obtain measurement results. In Comparative Examples 30 and 31, the image sticking evaluation parameter S R Because the value exceeded 9.00, seizure occurred on the contact surface of the evaluation material before the cut-off number of repetitions, and appropriate measurement results could not be obtained. In Comparative Example 32, the crowning R of the mating material 22 is less than 1mm, and the crowning radius 22 As a result of contact with the evaluation material at any position other than the position having the mark, no measurement results could be obtained. In Comparative Example 33, the load exceeded 15 kN, so the seizure evaluation parameter SR The yield parameter R exceeded 12.50, and by the end of the test, seizure had occurred on the contact surface of the test material, making it impossible to obtain appropriate measurement results. D Since the repetition rate was also greater than 0.85, the repetition rate was 1 × 10 6 After this period, plastic deformation occurred inside the evaluation material. In Comparative Example 34, since the sliding ratio of the evaluation material was lower than 60%, the contact surface of the evaluation material did not experience pitting until the number of repeated tests reached the cutoff number. In Comparative Example 35, since the slip ratio of the evaluation material was lower than -300%, seizure occurred on the contact surface of the evaluation material before the cut-off number of repetitions was reached, and appropriate measurement results could not be obtained. In Comparative Example 36, the sliding ratio of the evaluation material was higher than -60%, so that the contact surface of the evaluation material did not experience pitting until the number of repeated tests reached the cutoff number.

[0132] <Example 2> [Production of evaluation materials] The evaluation materials were manufactured by the following method. Steels SCr420, SCM420, SCM435, SCM822, SNCM220 and SACM645, which have chemical compositions conforming to the JIS G 4053 standard, were melted in a 300 kg vacuum melting furnace to produce molten steel, and each molten steel was cast to produce an ingot. The ingot was hot forged into a round bar with a diameter of 250 mm. Hot forging was performed at a temperature between 1100°C and 1200°C, and after forging, the bar was allowed to cool in the air. Each steel bar (vacuum melted material) was normalized in accordance with JIS B 6911:2010 "Normalizing and annealing processing of steel".

[0133] Next, each of the normalized steel bars having a diameter of 250 mm was machined to produce evaluation materials having the shapes shown in FIG. 9 and Table 4.

[0134] [Table 4]

[0135] The prepared evaluation materials were subjected to surface hardening heat treatment by gas carburizing, vacuum carburizing, or nitriding. The conditions for gas carburizing, vacuum carburizing, and nitriding were as follows. That is, in the gas carburizing treatment (gas carburizing quenching and tempering), each evaluation material was held at 930°C for 80 minutes in an atmosphere with a carbon potential CP of 1.0% (carburizing process). Then, the carbon potential CP was set to 0.8%, and the rough test pieces were held at 930°C for 60 minutes (diffusion process). Then, each evaluation material was cooled to 850°C, held at 850°C for 30 minutes, and then cooled in oil at 60°C (quenching process). After cooling, each evaluation material was subjected to tempering treatment. The tempering temperature was 180°C, and the holding time at the tempering temperature was 120 minutes. In the vacuum carburizing treatment, first, a carburizing process was carried out in which acetylene gas was introduced at a furnace pressure of 100 Pa or less. The temperature of the carburizing process was 930°C and the holding time was 30 minutes. After the carburizing process, the diffusion process was carried out. In the diffusion process, the introduction of acetylene gas was stopped and the pressure inside the furnace was set to 10 Pa or less. In the diffusion process, the temperature was 930°C and the holding time was 10 minutes. After the diffusion process, the quenching process was carried out. In the quenching process, the temperature was 850°C and the holding time was 30 minutes. After the holding time, the material was cooled in oil at 60°C. After the quenching process, the tempering process was carried out. In the tempering process, the temperature was 180°C and the holding time was 120 minutes. In the nitriding process, NH3, H2, and N2 gases were introduced into the furnace under atmospheric pressure and held at 570°C for 180 minutes. After the holding time, the material was cooled in oil at 60°C. The Vickers hardness Hv was measured by obtaining 10 cross sections at the contact part of the evaluation material and measuring the hardness distribution. In detail, in each cross section, starting from a position 0.03 mm in the depth direction from the contact surface, the Vickers hardness Hv is measured at 0.05 mm, 0.10 mm, and then every 0.05 mm to a depth of 2.00 mm in accordance with JIS Z2244:2020 under a load of 0.20 kgf. The measurement positions are three positions every 120 degrees on the cross section, and the average value of the radial length (depth) up to the position where the measured Vickers hardness Hv is 513 Hv is defined as the effective hardened layer depth D c It was decided.

[0136] [Manufacturing of counterpart materials] The mating material was manufactured by the following method: Using steel that meets the SCM420 standard of JIS G 4053:2016, the mating material shown in Figure 10 and Table 4 was manufactured by the general manufacturing process, that is, "normalizing → test piece processing → eutectoid carburizing in a gas carburizing furnace → low-temperature tempering → polishing."

[0137] The Vickers hardness Hv at a position 0.05 mm from the surface of the mating material, i.e., at a depth of 0.05 mm, was 740 to 760, and the depth at which the Vickers hardness Hv was 513 was in the range of 0.8 to 1.0 mm. The Vickers hardness Hv at a position 0.05 mm deep and the depth at which the Vickers hardness Hv was 513 for each evaluation material were measured in the same manner as in Example 1.

[0138] [evaluation] The evaluation of seizure and plastic deformation of each evaluation material produced was performed by the following method. After finishing the main body of the evaluation material in order to remove the heat treatment strain, the evaluation material and the mating material were subjected to a two-cylinder rolling fatigue test. The contact surface of the evaluation material and the contact surface of the mating material were brought into contact with each other, and after applying the contact pressure p0 shown in Table 5, they were rotated in opposite directions at the rotation speed shown in Table 5. The contact pressure p0 shown in the table was calculated by replacing πab in the above formula (11) with 2wL.

[0139] The number of cycles until the termination of the twin cylinder rolling fatigue test and the occurrence of plastic deformation inside the evaluation material during the test were confirmed in the same manner as in Example 1. The results are shown in Table 5.

[0140] [Table 5]

[0141] As described above, the contact width L in the axial direction, the contact width w in the circumferential direction, and the slip ratio σ 12 Using the above, the image sticking evaluation parameter S is calculated using the formula (1). R is 9.00 or less, and the conjugate maximum shear stress τ of the evaluation material is xyAt a depth position Dτ from the contact surface of the evaluation material, xy Dτ calculated from equation (4) using xy ' and the effective hardened layer depth D of the evaluation material c and the yield parameter R calculated from equation (5) D In the example where is 0.85 or less, no burn-in occurs, and the 6 After the repeated stress cycle, no plastic deformation (yielding) occurred inside the evaluation material. Therefore, the evaluation parameter S R is less than 9.00, and the yield parameter R D It was found that the two-cylinder rolling fatigue test with a coefficient of friction of 0.85 or less can evaluate the rolling fatigue strength of surface-hardened steels used in gears more simply and accurately.

[0142] In Comparative Example 59, the image sticking evaluation parameter S R Because the value exceeded 9.00, seizure occurred on the contact surface of the evaluation material before the cut-off number of repetitions, and appropriate measurement results could not be obtained. Comparative Example 60 has a yield parameter R D was greater than 0.85, so the number of iterations was 1 × 10 6 Therefore, even if the test was continued up to the cutoff number of cycles, it would not be possible to obtain appropriate measurement results. In Comparative Example 61, the radius R of the evaluation material 11 The measurement was small, at 1 mm, and the evaluation material was damaged during testing, making it impossible to obtain measurement results. In Comparative Example 62, since the slip ratio of the evaluation material was lower than -300%, seizure occurred on the contact surface of the evaluation material before the cut-off number of repetitions was reached, and appropriate measurement results could not be obtained. In Comparative Example 63, the sliding ratio of the evaluation material was higher than -60%, so that the contact surface of the evaluation material did not experience pitting until the number of repeated tests reached the cutoff number. In Comparative Example 64, the axial length of the mating material l 21 Because the size was only 1 mm, the pitting could not be detected and no measurement results could be obtained. In Comparative Example 65, the load exceeded 15 kN, so the seizure evaluation parameter S R The yield parameter R exceeded 9.00, and by the end of the test, seizure had occurred on the contact surface of the test material, making it impossible to obtain appropriate measurement results. D Since the repetition rate was also greater than 0.85, the repetition rate was 1 × 10 6 After this period, plastic deformation occurred inside the evaluation material. In Comparative Example 66, since the diameter D of the mating material was as small as 2 mm, pitting could not be detected and no measurement results could be obtained. In Comparative Example 67, the image sticking evaluation parameter S R Because the value exceeded 9.00, seizure occurred on the contact surface of the evaluation material before the cut-off number of repetitions, and appropriate measurement results could not be obtained.

[0143] In this way, the present invention includes a first rotation drive mechanism, a second rotation drive mechanism, a load application mechanism, a pitching detection unit, and a control unit, and detects the diameter D of the second rotation surface of the mating member, the distance x between the second rotation surface and the first rotation axis, the load, and the slip ratio σ 12 , image sticking evaluation parameter S R , and the yield parameter R D The fatigue test conditions are set while adjusting within an appropriate range. This makes it possible to provide an apparatus that can suppress seizure on the surface of the material to be evaluated and avoid internal plastic deformation, even when conducting tests under high loads (slip ratio, high surface pressure, and high rotational speed), and that can evaluate the suitability of steel materials under higher loads than ever before.

[0144] Although the preferred embodiment of the present invention has been described in detail above with reference to the accompanying drawings, the present invention is not limited to such an example. It is clear that a person having ordinary knowledge in the technical field to which the present invention pertains can conceive of various modified or altered examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally belong to the technical scope of the present invention. [Explanation of symbols]

[0145] C1 Center line, rotation axis 111 First surface of revolution 1, 1A, 1B Evaluation materials 301 First rotation axis 300 First rotary drive mechanism 401 Second rotation axis 402 Second surface of revolution 400 Counterpart 500 Second rotary drive mechanism 600 Load loading mechanism 700 Pitching detector 900 Control section

Claims

1. A test apparatus for evaluating the rolling fatigue strength of an evaluation material having a first rotation surface formed around a center line, comprising: a first rotation drive mechanism that holds the evaluation material and rotates the evaluation material about a first rotation axis that is coaxial with the center line; a mating member having a second surface of rotation centered on a second axis of rotation; a second rotation drive mechanism that holds the mating member so that the second rotation axis is parallel to the first rotation axis and rotates the mating member about the second rotation axis; a load applying mechanism that rotates the first rotational surface and the second rotational surface in opposite directions while opposing each other, and moves the first rotational drive mechanism and the second rotational drive mechanism closer to and farther from each other; A pitting detection unit that detects pitting occurring on the first rotation surface of the evaluation material; a control unit that controls the first rotation drive mechanism, the second rotation drive mechanism, and the load applying mechanism; Equipped with The diameter D of the second rotation surface of the mating member is 4 mm to 200 mm, During a rolling fatigue strength test in which a load is applied from the counter member to the evaluation member by the load application mechanism while performing the reverse rotation, a distance x between the second plane of rotation and the first axis of rotation is 2 mm to 100 mm; the control unit controls the load application mechanism so that the load is within a range of 0.2 kN to 15 kN; The control unit controls the first rotation drive mechanism, the second rotation drive mechanism, and the load application mechanism, The slip ratio σ of the evaluation material calculated by the following (Equation 1) 12 is set to -300% to -60% or 60% to 100%, The image sticking evaluation parameter S is calculated by the following formula (2): R is set to 9.00 or less A rolling fatigue strength testing device comprising: σ 12 = [%] = (2 × π × R 11 × u 1 / 60 - 2 × π × R 21 × u 2 / 60) / (2 × π × R 11 × u 1 / 60) ··· (Equation 1) S R =A(σ 12 / 100) 2 ・・・ (formula 2) R 11 : Radius of the first surface of rotation from the first axis of rotation [mm] R 21 : Radius of the second surface of rotation from the second axis of rotation [mm] u 1 : Rotation speed of the evaluation material [rpm] u 2 :Rotational speed of the mating material [rpm] A: Contact area [mm 2 ]

2. The root mean square roughness Rq of the contact surface of the evaluation material that comes into contact with the counter material and the contact surface of the counter material that comes into contact with the evaluation material is 1.00 μm or less, During the rolling fatigue strength test, the control unit controls the first rotation drive mechanism, the second rotation drive mechanism, and the load application mechanism, The yield parameter R calculated from the following (Equation 3) D is set to 0.85 or less, 2. The rolling fatigue strength testing device according to claim 1, R D = Dτ xy ' / D c …………(Formula 3) Dτ xy '=2×Dτ xy …………(Formula 4) Where: R D : Conjugate maximum shear stress τ of the evaluation material xy At a depth position Dτ from the contact surface of the evaluation material, xy Dτ calculated from the above (Equation 4) using xy ' and the effective hardened layer depth D of the evaluation material c and the yield parameter calculated by

3. The radius R of the first surface of revolution 11 is 2 to 100 mm 3. The rolling fatigue strength testing device according to claim 2, wherein the rolling fatigue strength testing device is a bearing.

4. The diameter D of the second rotation surface of the mating member is 4 mm to 200 mm, an axial distance d between the first rotation axis and the second rotation axis is 20 mm to 58 mm; The y value calculated by the following formula (5) is 0.75 or less.

4. The rolling fatigue strength testing device according to claim 1, wherein the rolling fatigue strength testing device is a bearing. y=2d / D-1...(Formula 5)

5. The crowning radius of the mating member 22 is 1 mm or more 2. The rolling fatigue strength testing device according to claim 1,

6. The second rotational axis of the mating member is parallel to the second rotational axis of the mating member. 22 Length dimension l excluding the part 21 is 2 mm or more 6. The rolling fatigue strength testing device according to claim 5,

Citation Information

Patent Citations

  • Carbonitrided member, and method for producing carbonitrided member

    JP2010132936A